2023
DOI: 10.2147/jir.s392599
|View full text |Cite
|
Sign up to set email alerts
|

AVE 0991 Suppresses Astrocyte-Mediated Neuroinflammation of Alzheimer’s Disease by Enhancing Autophagy

Abstract: Purpose Our previous study has shown that AVE 0991, a nonpeptide analogue of Ang-(1-7), ameliorates cognitive decline and inhibits NLRP3 inflammasome of astrocytes in Alzheimer’s disease model mice. Additionally, several studies have suggested that activation of autophagy appears to effectively inhibit the progression of neuroinflammation. However, it is unclear whether AVE 0991 can modulate astrocyte autophagy to suppress neuroinflammation in Alzheimer’s disease. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Autophagy is essential for cellular differentiation, homeostasis, and survival [ 91 , 92 ] and is conserved across evolution. Recent studies have shown that altered autophagy is involved in neuroinflammation processes in many neurological diseases, including Parkinson’s disease [ 93 , 94 ], Alzheimer’s disease [ 95 , 96 ], and neuropathic pain [ 67 , 97 , 98 ]. It was reported that autophagic activity in microglia in the spinal cord was suppressed in animals with neuropathic pain from day 2 to day 28 after nerve injury [ 99 ].…”
Section: Downstream Signaling Molecules Used By Ezh2 To Regulate Neur...mentioning
confidence: 99%
“…Autophagy is essential for cellular differentiation, homeostasis, and survival [ 91 , 92 ] and is conserved across evolution. Recent studies have shown that altered autophagy is involved in neuroinflammation processes in many neurological diseases, including Parkinson’s disease [ 93 , 94 ], Alzheimer’s disease [ 95 , 96 ], and neuropathic pain [ 67 , 97 , 98 ]. It was reported that autophagic activity in microglia in the spinal cord was suppressed in animals with neuropathic pain from day 2 to day 28 after nerve injury [ 99 ].…”
Section: Downstream Signaling Molecules Used By Ezh2 To Regulate Neur...mentioning
confidence: 99%
“…Therefore, autophagy has emerged as one of the most important mechanisms that regulate NLRP3 inflammasome [15,16]. Some recent studies have shown that induction of autophagy by pharmacological or non-pharmacological means can help mitigate NLRP3 inflammasome mediated or other types of inflammation [17][18][19][20]. Therefore, targeting NLRP3 inflammasome and autophagy together can be a good strategy, particularly when most of the monotargeted therapies have not shown any significant clinical advantage for treating AD.…”
Section: Introductionmentioning
confidence: 99%